Magnetic resonance spectroscopic imaging. - Nelson, S.J.
Gliomas are infiltrative primary brain tumors that are extremely heterogeneous in terms of both their imaging characteristics and response to therapy. Anatomic magnetic resonance (MR) images are limited in terms of their ability to evaluate the spatial extent of the lesion and to distinguish recurrent tumor from treatment-induced necrosis. An in vivo molecular imaging technique that has shown promising results for assisting in the evaluation of gliomas is MR spectroscopic imaging (MRSI). Examples of these data are presented and compared with results obtained from diffusion-weighted and perfusion-weighted MR images.
Keywords: Anatomic magnetic resonance images; Diffusion-weighted MR images; Gliomas; Imaging characteristics; In vivo molecular imaging; Infiltrative primary brain tumors; Lesion; Magnetic resonance spectroscopic imaging; Perfusion-weighted MR images; Recurrent tumor; Therapy; Treatment-induced necrosis